2020
DOI: 10.2169/internalmedicine.4723-20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Snoring and Lifestyle-related Diseases among a Japanese Occupational Population

Abstract: Objective Snoring is a common physical condition in active workers. However, the link between snoring and health problems is poorly understood. Therefore, the prevalence of snoring in Japanese workers and the relationships between snoring and lifestyle-related diseases were investigated. Methods This was a retrospective, single-center, cross-sectional study. The results of a single year's medical examinations were investigated for 25,141 Japanese active office workers 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…The prevalence of snoring was 20% among Japanese workers. [ 21 ] In addition, another study assessed the prevalence of snoring in a university population in Saudi Arabia and found that 19.2% of the participants snore. [ 7 ] However, the prevalence of snoring does not necessarily indicate the development of obstructive complications, but these findings emphasize the need for awareness about the possible complications of snoring.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of snoring was 20% among Japanese workers. [ 21 ] In addition, another study assessed the prevalence of snoring in a university population in Saudi Arabia and found that 19.2% of the participants snore. [ 7 ] However, the prevalence of snoring does not necessarily indicate the development of obstructive complications, but these findings emphasize the need for awareness about the possible complications of snoring.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between snoring and hypertension has been shown in several studies, 13,14 especially in men, 15,16 which may elevate the risk of CVD, with CHD as one of its manifestations. The association may result from intermittent hypoxia-induced sympathetic activation, oxidative stress and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 91%
“…Management and Healthcare Policy 2022:15 Cox Regression and LASSO Regression to Extract Predictors Twenty variables were filtered by the Cox regression and LASSO regression method (Table2). In univariate analysis, sex, age, duration of hypertension, smoking, BMI, NC, WC, SBP, diabetes, TC, HDL, LDL, FPG, AHI, minimum SaO 2 and kinds of antihypertensive drugs at discharge were associated with the occurrence of CHD.…”
mentioning
confidence: 99%
“…Snoring exacerbates atherosclerosis and vascular remodeling independent of OSA and other cardiovascular risk factors [ 10 , 11 ]. Simple snoring alone is still significantly associated with metabolic syndrome after controlling for the effects of recurrent apnea and hypoxia [ 12 ] Snoring is also associated with dyslipidemia in some individuals [ 13 , 14 ]. Therefore, further research needs to be conducted to clarify the association between snoring and dyslipidemia in the general population.…”
Section: Introductionmentioning
confidence: 99%